Sildenafil improves exercise capacity in patients with cystic fibrosis: a proof-of-concept clinical trial. (November 2019) - Rodriguez-Miguelez, Paula; Ishii, Haruki; Seigler, Nichole; Crandall, Reva; Thomas, Jeffrey; Forseen, Caralee; McKie, Kathleen T.; Harris, Ryan A.
Background: Exercise intolerance is a common phenotype observed in patients with cystic fibrosis (CF). Treatment with sildenafil, a phosphodiesterase type 5 (PDE5) inhibitor, has previously been shown to improve exercise capacity (VO2 peak) in other patient populations. Thus, the present study sought to determine the acute and subacute effects of sildenafil on exercise capacity in patients with CF. Methods: The present investigation utilized a randomized, double-blind, placebo-controlled, crossover study with an acute dose of either sildenafil (50 mg) or placebo ( n = 13, age 25 ± 10), followed by a 4 week open-label extension with sildenafil (20 mg, TID; n = 15, age 23 ± 11). A comprehensive evaluation of pulmonary function and a maximal exercise test were each performed at every visit. Results: A significant increase in VO2 peak was observed after the acute sildenafil dose with no changes following placebo (77 ± 13 versus 72 ± 13% predicted; p = 0.033). In addition, after 4 weeks of treatment, patients showed a significant increase in exercise capacity (72 ± 12 versus 75 ± 12% predicted; p = 0.028) and exercise duration (409 ± 98 versus 427 ± 101 s; p = 0.014). A robust correlation ( r = 0.656; p = 0.008) between baseline FEV1 (% predicted) and the change in exercise capacity following 4 weeks of treatment was identified. Conclusions: This proof-of-concept clinical trial demonstrates that sildenafil treatment can improve exercise capacity in patients with CF and that pulmonary function may play an important role in the effectiveness of treatment. Future investigations of sildenafil treatment in patients with CF are certainly warranted.